Application of blockchain in telecom operators - Yunyong ZHANG; Gang CHENG; Gang AN; Xuehong YANG; Guixiang ZOU (Dianxin kexue)
Blockchain is another disruptive technological revolution after the IoT,cloud computing and big data.Blockchain technology and typical application cases were firstly introduced,and then the role of blockchain technology and blockchain in operators were analyzed.Secondly,combined with the characteristics of the blockchain,the application of blockchain in multiple operators were focused on,such as infrastructure,international roaming settlement,digital points issuance and trading,data storage,cross-border payment,identity verification,and credit reporting.Finally,the challenges faced by operators in the comprehensive application of blockchain were introduced.